Notes on poietics as a methodological approach to art research (Revista Apotheke, 2024)
This article aims to analyze the foundations of poietics as a methodological approach to research in Art. After a succinct conceptual separation and a brief historical review of the terminology and its uses, it investigates the perspective proposed by Dr.ª Sandra Rey for the application of that. It was noticed, therefore, that the poietic approach, in addition to making transits between the instances of research in Art more flexible, is sometimes confused with the genesis of research in visual poetics.
Keywords: visual arts; research in art; methodological approach; poietics; Sandra Rey